1988
DOI: 10.2118/15563-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Study of a Coupling Mechanism Between Longitudinal and Torsional Drillstring Vibrations at the Bit

Abstract: Summary. A mechanism that couples longitudinal and torsional drillstring vibrations at the bit was studied. Torsional vibrations are associated with dynamic variations of the rotational bit speed. When a roller bit runs over a multilobed pattern, these speed variations have been shown to affect the input of longitudinal vibrations. The theory for this coupling mechanism is verified experimentally by high-rate data of near-bit accelerations and torque recorded in a 1000-m [3,280-ft] -deep well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…His analyses demonstrated that conventional PDC bits tend to whirl backward, while anti-whirl PDC bits effectively reduce this tendency and whirl forward. The possibility to vibrate with backward and forward whirlings was noted also by Schen et al [11] and Thor Viggo and Age [12]. In their observations, the whirl rotation occurred several times per revolution of the bit and during whirl, the bit drilled an overgage hole with a multilobed cross-section.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…His analyses demonstrated that conventional PDC bits tend to whirl backward, while anti-whirl PDC bits effectively reduce this tendency and whirl forward. The possibility to vibrate with backward and forward whirlings was noted also by Schen et al [11] and Thor Viggo and Age [12]. In their observations, the whirl rotation occurred several times per revolution of the bit and during whirl, the bit drilled an overgage hole with a multilobed cross-section.…”
Section: Introductionmentioning
confidence: 68%
“…The techniques used for analysis of equation system (1), (3), (4), (12), and (21), as stated above, represent an implicit computational algorithm of integration. It is absolutely stable for any time increment t ∆ of the integration process but to provide the satisfactory accuracy, it should be fairly small.…”
mentioning
confidence: 99%
“…For the drilling industry, comprehensive experimental facilities have been developed to characterize the bit performance. 99 These facilities have improved the understanding of the interaction between the drill bit and rock formation, resulting in high performance drilling tool and proper operation. The investigations reviewed in the following section focuses on the experimental studies of stick–slip vibrations in drillstring.…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Other experimental drillstrings constructed for laboratory investigations have been reported in the literature. Aarrestad and Kyllingstad [12,13] constructed a full-scale 1000 m vertical research drillstring for studying the coupling between axial and torsional vibrations at the BHA. They used a vertical drillstring and utilized a hard-wire measurement-while-drilling (MWD) tool.…”
Section: Introductionmentioning
confidence: 99%